Problems and Obstacles on working process of Community Justice Center in a sub-district in Chiang Rai Province - Bungkrai, Weerapong; Pollamai, Avika (Journal of Thai Justice System, 2020)
The implementation of community justice locally, according to the immediate policy created by the Ministry of Justice, through establishing a “Community Justice Center” in a sub-district of every province may cause operation problems in terms of its readiness. For example, the case study of Chiang Rai Province, undertaken in the fiscal year of B.E. 2562, By interviewing personnel related to the operations of the Community Justice Center shows that; in the overall the Community Justice Center has faced obstacles and problems in relation to its operation. Such obstacles and problems are caused by the following factors: a lack of specific laws and budgets to support its activities, overlapping duties that contradict the authorities of subdistrict headmen/village chiefs, including other agencies with similar roles and duties; an insufficient understanding of the concept of community justice among the Center’s committees. Furthermore, the obstacles and problems include insufficient numbers of local administrative officials who help the Community Justice Center (some officials have been overwhelmed with their main duties and some have negative attitudes towards duties required by the Community Justice Center). In addition, there are safety risks when performing duties, including communication problems that arise when dealing with people of ethnic groups. These problems and obstacles impede the performance of the Community Justice Center in Chiang Rai Province and have resulted in the inability to meet the mission outlined by the Ministry of Justice with regard to Community Justice Centers. Thus, this research has main objective to explored possible solutions to lessen the arising problems with relation to the performance of the Community Justice Center in Chiang Rai Province. The research has the concluded the following: The local administrative organization, pursuant to the Announcement of the Decentralization to the Local Government Organization Committee, Re: “Guidelines on Community Complaint Management with relation to public services provided by the Provincial Administration Organization (PAO), the Municipality and Subdistrict Administration Organization (SAO), can financially support the operations of the Community Justice Center. In addition, in order to motivate the local administrative organization to drive the missions of the Community Justice Center, the Office of The Permanent Secretary for Ministry of Justice shall consult with and seek co-operation from the Department of Local Administration to consider adding explanations and specifying key performance indicators and requirements for Local Performance Assessment. This interaction will cover every aspect of the missions provided by the Community Justice Center. Additionally, The Office of the Permanent Secretary for Ministry of Justice should clearly define the mission frameworks on complaint management. The Justice Provincial Office should take a proactive role in developing efficiency within the Community Justice Center’s committees. Lastly, relationships between justice networks should be established, especially co-operation between police officials in helping criminal victims and defendants in accordance with related laws.